(untitled) (Desenvolvimento em Questão, 2025)
The insertion of the Amazon in the capitalist world system, as well as Latin America as a whole, is crossed by modernity/ coloniality that, despite its metamorphoses, intensified in the second half of the twentieth century with the deepening of the idea of domination of nature and denial of peoples and communities that developed life forms imbricated to it. In the most recent period, the politicization of these subjects’ struggles, as well as the expansion of a perception of ecological crisis on a planetary scale, has placed the Amazon and its territorial disputes at the center of environmental geopolitics. In this perspective, the issue of regional planning in the Amazon has deepened its multiscalar dimensions and cannot be considered dissociated from the global hegemonic disputes around the international environmental agenda, that also crosses the disputes between the forces that polarize the Brazilian political scene. This article seeks to analyze the different positions regarding the environmental agenda related to the regional issue of the Amazon, presented in development plans linked to the last federal governments, that express not only the different conceptions between the agents who seek to dispute the block in the Brazilian power, as its limits and contradictions in the rupture with the coloniality that crosses the socio-spatial formation of the region.